2009
DOI: 10.1016/j.ceramint.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and aging of lead magnesium niobate in water

Abstract: Lead magnesium niobate (PMN) is an important relaxor ferroelectric material commonly employed in multilayer capacitor and actuator manufacturing owing to its high dielectric constant and superior electrostrictive properties. However, stability of this material in water is not very well known and there is need for a detailed investigation. In this research, solubility of lead magnesium niobate powders in water was determined as a function of solids concentration. The obtained results showed that the amount of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Although the rise in viscosity may be attributed to the complex formation between the divalent ions and the PAA there is also a possibility for a complex formation between MgCl 2 and PMN particle surface. According to the previous study of Deliormanli et al electrophoretic mobility measurements of the PMN suspensions showed that in the presence of MgCl 2 , as a background electrolyte, isoelectric point of PMN was depended on the salt concentration which means that there is Mg 2+ adsorption onto the surface [39]. Similar results were obtained for PAA-coated PMN suspensions containing zinc acetate.…”
Section: Gelation With Ionic Strength Modificationsupporting
confidence: 75%
See 2 more Smart Citations
“…Although the rise in viscosity may be attributed to the complex formation between the divalent ions and the PAA there is also a possibility for a complex formation between MgCl 2 and PMN particle surface. According to the previous study of Deliormanli et al electrophoretic mobility measurements of the PMN suspensions showed that in the presence of MgCl 2 , as a background electrolyte, isoelectric point of PMN was depended on the salt concentration which means that there is Mg 2+ adsorption onto the surface [39]. Similar results were obtained for PAA-coated PMN suspensions containing zinc acetate.…”
Section: Gelation With Ionic Strength Modificationsupporting
confidence: 75%
“…The solubility of these cations from the surface reaches maximum especially at pH < 3. On the other hand, Nb 5+ have a rather low dissolution under the same conditions [39]. Furthermore, during acid titration the reactivity of PMN particles may lead to a time dependent pH rise and this cause partial restabilization of the PMN suspensions.…”
Section: Gelation With Ph Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7a, b shows the FTIR spectra of the LPMO powders in the range of 600-4,000 cm -1 , fresh xerogels and calcined at 650°C, respectively. The FTIR spectrum is similar to the most other ABO 3 -type perovskite compounds which have common BO 6 oxygenoctahedral structure [22][23][24]. Two samples show the typical M-O-C pair vibrations around 1,385 and 1,593 cm -1 [25].…”
Section: Ir Spectramentioning
confidence: 55%
“…Another explanation for the decrease observed in lead amount may due to the complex formation such as PbOH or Pb 4 ðOHÞ 4 4 . [29] Figures 8 and 9 demonstrate the effect of PAA=PEO comb polymers and PAA on the solubility of PMN as a ion concentration in solution at pH 6 and pH 9. Furthermore, an increase was observed in Pb þ2 and Mg þ2 concentrations in solution as the polyelectrolyte concentration increase.…”
Section: Cation Dissolution From Pmn In the Presence Ofmentioning
confidence: 99%